REKONSTRUKSI REGULASI BARANG KIRIMAN IMPOR SEBAGAI BENTUK PERLINDUNGAN HUKUM BAGI USAHA MIKRO, KECIL, DAN MENENGAH - Juliana Juliana; Rusdianto Sesung; Febrian Rizki Pratama (Journal of Innovation Research and Knowledge, 2026)
Micro, Small and Medium-sized Enterprises (MSMEs) in Indonesia face the threat of large volumes of imported goods exploiting loopholes in customs regulations. This study aims to analyse the vagueness of the phrase ‘per consignee per consignment’ in Article 29 (2) of Regulation of the Minister of Finance of the Republic of Indonesia No. 96 of 2023, as amended by Regulation of the Minister of Finance of the Republic of Indonesia No. 4 of 2025, and to formulate a legal reconstruction of the article in order to provide protection for MSMEs. This normative legal study employs two approaches: the statutory approach and the conceptual approach. The findings indicate that the current provision suffers from vagueness due to the absence of measurable restrictions on frequency, quantity of goods, and identity verification. Importers exploit this loophole in customs law by splitting documents to obtain exemption from import duties below the de minimis threshold of USD 3.00, which harms the domestic MSME market and undermines the principle of corrective justice. It is therefore necessary to amend this article by introducing restrictions on frequency, quantity of goods, and verifiable identity checks. These identity checks must be integrated in real time via the Customs-Excise Information System and Automation (CEISA) with the databases of the Directorate General of Civil Registration and Population (Dukcapil) and the Directorate General of Taxes. This revision of the legal substance is urgently needed to close loopholes that allow for the misuse of customs facilities, whilst also providing preventative legal protection and legal certainty for the sustainability of MSMEs, in accordance with the mandate of Article 33 of the 1945 Constitution of the Republic of Indonesia